Basic Training Kewirausahaan: Perencanaan Dan Pemasaran Kreatif Untuk Bisnis Start Up Bagi Pemuda-Pemudi Usia Produktif Pelaku Usaha Di Kota Jayapura - Kurniawan Patma; Rudiawie Larasati (UNIVERSITAS CENDERAWASIH, 2022)
This community service activity is about entrepreneurship education for young people in Jayapura City who are start-up entrepreneurs to improve their related skills by planning and marketing business products creatively and productively. This activity is divided into 2 stages: (1) Focus Group Discussion with a team of facilitators and co-facilitators and (2) Training for young entrepreneurs start-up. Location of this activities for Focus Group Discussion through Ms.Teams virtual media and face-to-face training in the Master of Accounting Uncen hall. The result of this community service provides a stimulus to young people in Jayapura City related to this activity. By this activity, the entrepreneurial spirit needs to be applied through activities empowerment, and this activity stimulates participants with planning, bookkeeping and good marketing.